Design and Experimental Test of a self-sealing component for reciprocal motion of MR fluid based device - Van Cuong Vo; Hai Zy Zy Le; Qui Duyen Do; Quoc-Hung Nguyen (Results in Engineering, 2024)
This research presents a novel approach to sealing components by proposing an optimized design and experimental evaluation of a magneto-rheological fluid (MRF) sealing component for reciprocal motion, with a specific focus on MR dampers. The traditional O-ring is replaced by a continuously activated MRF seal using an axial permanent magnet. The paper begins with a comprehensive overview of previous research on the application of MR fluid in sealing and presents a proposed configuration for a MRF based seal (MRF seal shortly) for reciprocal motion. Optimal design and modeling of the MRF seal are performed through finite element analysis, and a prototype is manufactured for experimental testing. The performance characteristics of the MRF seal are thoroughly investigated based on both experimental and simulated results. The study evaluates the effectiveness of the MRF seal in terms of its sealing capability and durability. The findings of this research have potential applications across various industries that require sealing components for reciprocating motion, including automotive, aerospace, and manufacturing. By embracing this innovation, these industries can achieve significant energy savings by minimizing friction and enhancing overall operational efficiency.